Evolving Practice Pattern of Palliative Radiation Therapy for Bone Metastases from Lung Cancer in Australia. Issue 12 (December 2021) - Ong, W.L.; Ball, D.L.; Milne, R.L.; Foroudi, F.; Millar, J.L.
Abstract: Aims: Radiation therapy is an effective treatment for bone metastases. Single-fraction conformal radiation therapy (SF-CRT) is equally effective as multifraction radiation therapy for the management of uncomplicated bone metastases. There has been a rapid development of advanced radiation therapy techniques (ART) in radiation oncology. We evaluated the changing pattern of SF-CRT and ART use for the management of bone metastases in lung cancer. Materials and methods: This was a state-wide population-based cohort of lung cancer patients from Victoria, Australia, who received radiation therapy for bone metastases between 2012 and 2017. The primary outcomes were proportion of radiation therapy courses using: SF-CRT and ART. We identified a subcohort in which radiation therapy was delivered at the end of life (EOL), i.e. within 30 days of death. The Cochran–Armitage test for trend was used to evaluate the change in pattern of SF-CRT and ART use over time. Multivariable analyses were used to identify factors associated with the primary outcomes. Results: Of the 4335 courses of radiation therapy for bone metastases in lung cancer, 20% were SF-CRT – increasing from 19% in 2012 to 26% in 2017 ( P -trend = 0.004). In multivariate analyses, treatment to the rib, shoulder, hip or extremities, and treatment in public institutions were independently associated with SF-CRT use, but the effect of year of radiation therapy was no longer significant. Five per cent of radiation therapy was delivered using ART, increasing markedly from 2016 onwards ( P -trend < 0.001). In multivariate analyses, treatment in private institutions and more recent years of treatment were independently associated with the use of ART. There were 587 courses of radiation therapy delivered at the EOL, with SF-CRT more commonly used closer to death – 53%, 29% and 25% of radiation therapy within 7 days, 8–14 days and 15–30 days of death, respectively. Conclusion: SF-CRT continued to be underutilised for bone metastases in lung cancer in Australia, including at the EOL. We observed an increase in ART use for bone metastases from 2016, which occurred contemporaneously with changes in government funding. Highlights: Only one in five courses of palliative radiation therapy for bone metastases in lung cancer were single fraction. One in two courses of palliative radiation therapy for bone metastases in the last week of life were multifraction. There was a marked increase in use of advanced radiation therapy techniques for bone metastases.